2018
DOI: 10.1063/1.5011109
|View full text |Cite
|
Sign up to set email alerts
|

Highly conductive ultrathin Co films by high-power impulse magnetron sputtering

Abstract: Ultrathin Co films deposited on SiO 2 with conductivities exceeding that of Cu are demonstrated. Ionized deposition implemented by high-power impulse magnetron sputtering (HiPIMS) is shown to result in smooth films with large grains and low resistivities, namely 14 µΩ cm at a thickness of 40 nm, which is close to the bulk value of Co. Even at a thickness of only 6 nm a resistivity of 35 µΩ cm is obtained. The improved film quality is attributed to a higher nucleation density in the Co-ion dominated plasma in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…It has been reported that Cu and W, , which are currently used for local interconnect, rapidly increase resistivity based on thickness scaling at several tens of nanometers. Even in the case of Ru and Co, , which are next-generation wiring materials with low resistivity, an increase in resistivity was mostly observed at the level of 10 nm, and there was no report that the resistivity was maintained up to a thickness of below 5 nm. Therefore, the MoC x thin film deposited using the IM-02 can be very attractive as a new material that can solve issues such as RC delay, increased power consumption, and increased noise in highly scaled devices with metal line widths reduced to the sub-10 nm scale.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Cu and W, , which are currently used for local interconnect, rapidly increase resistivity based on thickness scaling at several tens of nanometers. Even in the case of Ru and Co, , which are next-generation wiring materials with low resistivity, an increase in resistivity was mostly observed at the level of 10 nm, and there was no report that the resistivity was maintained up to a thickness of below 5 nm. Therefore, the MoC x thin film deposited using the IM-02 can be very attractive as a new material that can solve issues such as RC delay, increased power consumption, and increased noise in highly scaled devices with metal line widths reduced to the sub-10 nm scale.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 Thus, thin films with excellent properties can be obtained via BP-HiPIMS. 23,24 Figure 1a shows the voltage pulses applied to the sputter target in BP-HiPIMS. A negative voltage sputter pulse (T1) followed by a positive voltage pulse (T3) is applied to the sputter target.…”
Section: Bipolar High-power Impulse Magnetron Sputteringmentioning
confidence: 99%
“…A possible explanation is that the film is nanocrystalline and the crystallinity cannot detected in h-2h scans, although it may be detected by grazing-incidence x-ray diffraction (GIXRD). 32 The cobalt signal emerges after annealing the film at 600 C at 2h ¼ 44:3 , correspondig to cubic (111), and around 2h ¼ 52 , corresponding to cubic (200). 26 The film likely forms large polycrystalline grains at this anneal temperature that can be detected by the h-2h scan.…”
Section: Structural Characterizationmentioning
confidence: 99%